Antioxidant and antiproliferative effects of different Raphanus Sativus L. extracts - Tiraş, S; Kaya Kartal, Y; Ercan, N; Sel, T (Journal of the Hellenic Veterinary Medical Society, 2024)
This study aimed to investigate the phenolic and flavonoid levels, antioxidant activities and antiproliferative effects of Japanese, Chinese, Black, and Kohlrabi radish species on HEK293 immortalized human embryonic kidney cells in cell culture medium. DPPH radical scavenging activity, total polyphenol, and flavonoid content of the extracts were measured spectrophotometrically. The highest total flavonoid content in sap of radish extraction and methanolic extraction was 0.12±0.02 mg/g RE and 0.10±0.00 mg/g RE in Chinese radish; the highest total polyphenol content was 0.32±0.03 mg/g GAE and 0.23±0.03 mg/g GAE in Black radish; the DPPH radical scavenging activity is approved 39.68±2.43 µg/g GAE in Japanese radish in sap of radish extraction and 84.59±3.50 µg/g GAE in Black radish in methanolic extraction respectively. DPPH radical scavenging activity was higher in the methanolic extraction of all radishes. The antiproliferative effects of different extracts in HEK293 cells were investigated by the MTT method. The IC50 concentration was found at lower doses in the methanolic extraction of whole radishes compared to the sap of radish extractions. The lowest dose of antiproliferative effect was observed in red radish (160 mg/ml) in methanolic extraction, and the antiproliferative effect increased dose-dependent. As a result, both antioxidant content and antiproliferative effect may vary depending on the type of radish, soil, and geographical conditions of the region where it is grown.